SEMANTIC AND ARTISTIC INTERPRETATION OF "FAUST" AS A GENRE OF TRAGEDY - Omonturdiyeva Nazokat Kurban's kizi,; Jummayeva Zulfia Bahromovna, (Лучшие интеллектуальные исследования, 2023)
Abstract: The article examines the translation and creative retrospective of the reception of Goethe's tragedy "Faust" in Russian literature of the first third of the 19th century. The first translation of “Dedication” from Goethe’s tragedy V.A. Zhukovsky “Dream. Imitation of Goethe" and "Offering", which was not published during his lifetime. Free translation of “Prologue in the Theater” by A.S. Griboyedov from the first part of Goethe’s Faust, as well as the original epigram “How magazine brawls spread!”